Crime Settlement of Khalwat in Aceh - Syihab, Mahdi Abdullah (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Khalwat (Seclusion) is a despicable act that violates Islamic law because it leads to adultery. However, Qanun No. 6 of 2014 concerning Jinayat Law stipulates that the settlement of khalwat must go first through the Customary Court so that the punishment applied is not Islamic law punishment, such as ta`zir, but customary punishment.Purposes of the Research: This study aims to analyze the mechanism for resolving the crime of seclusion in Aceh.Methods of the Research: This is normative/doctrinal research using a statutory approach and a comparative approach.Results of the Research: Khalwat is a crime (jarimah) that violates Islamic law and it is categorized into jarimah ta`zir. Settlement of jarimah seclusion can be carried out by litigation through the Syar'iyah Court and the settlement goes to customary courts. However, Article 24 of Qanun Number 6 of 2014 concerning Jinayat Law, stipulates that the settlement of criminal acts of seclusion must first be through customary courts. The settlement mechanism for khalwat is first resolved through customary courts using a deliberation-consensus approach like village meetings, it is usually called Gampong Customary Meetings (RAG) by executing customary punishments such as penalties of paying fines, feasting, bathing, and the khalwat couple is forced to get married. The consideration of implementing customary punishment is to solve the case more effectively and efficiently and in return can raise the level of trust and community compliance.